Antioxidants Reduce Tissue Necrosis in The Zone of Stasis: Review of Burn Wound Conversion - Wardhana, Aditya; Halim, Jessica (Lingkar Studi Bedah Plastik Foundation, 2020)
Summary: Severe burns are devastating condition identified by loss of hemodynamic stability and intravascular volume. Adequate fluid replacement, nutritional support, and immediate wound grafting can reduce the risk of infection and mortality. Oxidative stress was shown to have significant role in the burn wound conversion, which happens when the zone of stasis can’t be salvaged and progresses to necrosis. Decreasing the level of oxidative stress early may be fundamental in reducing burn injury progression into deeper tissue. Several animal studies have demonstrated the advance of antioxidant supplementation for burns outcomes. Approach to this salvageable burn tissue is a breakthrough for new directions in burn management. Antioxidant supplementations was proven to prevent burn conversion on the ischemic zone. Administering antioxidant post-burn is linked with less progression of burn depth and inflammatory cytokine release, which alleviates burn-related morbidity and mortality and improves patient’s quality of life. To date, no clinical trials have been done to reproduce similar outcomes of this ROS-scavenging therapy as successfully observed in murine models. Antioxidant supplementation is a promising treatment avenue to halt burn wound conversion following severe burns. Keywords: Burn wound, wound conversion, burn management, antioxidant